Analysis of the Influence of Competence, Performance Allowances, Work Ethics on Accountability Through Transparency as Intervening Variables in Civil Servants in the Bantul Regional Government - Anggita Putri Rachmawati; Sri Hermuningsih; Gendro Wiyono (LP3M Universitas Putra Bangsa, 2023)
This analysis examines the phenomenon in the management of civil servants performance allowances that are not in accordance with financial governance, accountability and transparency because the civil servants performance management system is not in accordance with competence so that it affects work ethic. The study aims to analyze the partial effect of competence, performance allowances and work ethic on accountability and transparency in civil servants in Bantul Regional Government. This type of research is quantitative, using the survey method. Data collection using questionnaires with validity and reliability tests, descriptive and inferential data analysis methods. To get newness from previous researchers, researchers added mediation analysis using the path analysis method. This study used a sample of 88 civil servants who received performance allowances in Bantul Regional Government. The results of the study according to the hypothesis test show that competence, performance allowances and work ethic have a positive and significant effect on transparency and on the variables of competence, performance allowances and work ethic have a positive and significant effect on accountability.